Increasing pregnancy rates at first service in dairy cows exposed to high ambient temperatures before and after calving - J. A. Cartmill; Timothy G. Rozell; S. Z. El-Zarkouny; John F. Smith (Kansas Agricultural Experiment Station Research Reports, 1999)
Cows exposed to heat stress before or after calving or both are prone to reduced fertility because of reduced expression of estrus and less embryonic survival if pregnant. Cows calving on three dairy farms during the summer of 1998 were studied. First inseminations were programmed to occur between 50 and 70 days in milk using the Ovsynch protocol, which included a timed artificial insemination. Control cows were treated similarly but did not receive the second injection of gonadotropin-releasing hormone and were inseminated only after estrus was detected (Select Synch). The Ovsynch protocol increased pregnancy rates from 17.6 to 31.3%, because AI submission rates were 100% and conception rates were not different from those of control (Select Synch) cows.; Dairy Day, 1999, Kansas State University, Manhattan, KS, 1999;
Keywords: Dairy Day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-136-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 842; Dairy; Ovsynch protocol; Heat stress; Estrus